A Meta-Analysis of Sustanainability Development Goals (SDGs) During the Covid-19 Pandemic - Rifaid, Rifaid; Abdurrahman, Abdurrahman; Rahmi, Siti Atika; Kurniawan, Cahyadi (Universitas Pancasakti, 2024)
This study is a bibliometric analysis to determine the map of the development of the sustainability study of development goals during the COVID-19 pandemic by searching through Scopus with the keywords